Cindrella - Cloke; Rene (Nottinghamsphire AWARD PUBLICATIONS LIMITED, 2013)
Cinderella and the Colonel Cinderella may be a duchess, but her life is in tatters. Orphaned, destitute, and living in a country recovering from a hostile takeover, she is desperate to save her lands and servants. Unfortunately, her sacrifices aren$1 (Bt enough, and she is given one season to pay off her debts. All seems lost, until she is befriended by the debonair Colonel Friedrich$1 (Ba citizen of the oppressing country that now rules her homeland. Though Friedrich shamelessly flirts with her, Cinderella wonders if he is more than he appears to be. What if together they could unite their lands against the bitterness and resentment that threatens to destroy them?s